Psychometric Properties of the Deep Muscle Contraction Scale for Assessment of the Drawing-in Maneuver in Patients With Chronic Nonspecific Low Back Pain - Oliveira, Crystian B. [UNESP]; Negrao Filho, Ruben F. [UNESP]; Franco, Marcia R. [UNESP]; Morelhao, Priscila K. [UNESP]; Araujo, Amanda C.; Pinto, Rafael Z. [UNESP] (J O S P T, 2017)
STUDY DESIGN: A prospective cohort study. BACKGROUND: Motor control dysfunctions have been commonly reported in patients with chronic nonspecific low back pain (LBP). Physical therapists need clinical tools with adequate psychometric properties to assess such patients in clinical practice. The deep muscle contraction (DMC) scale is a clinical rating scale for assessing patients' ability to voluntarily contract deep abdominal muscles. OBJECTIVES: To investigate the intrarater reliability, floor and ceiling effects, internal and external responsiveness, and correlation analysis (with ultrasound measures) of the DMC scale in patients with chronic nonspecific LBP undergoing a lumbar stabilization exercise program. METHODS: Sixty-two patients with chronic nonspecific LBP were included. At baseline, self-report questionnaires were administered to patients and a trained assessor evaluated abdominal muscle recruitment with the DMC scale and ultrasound imaging. Four ratios of the change in abdominal muscle thickness between the resting and contracted states were calculated through the ultrasound measures. After 1 week, the same ultrasound measures and DMC scale were collected again for the reliability analysis. The proportions of patients with the lowest and highest scores on the DMC scale were calculated to investigate floor and ceiling effects. All patients underwent a lumbar stabilization program, administered twice a week for 8 weeks. After the treatment period, all measures were collected again, with the addition of the global perceived effect scale, to assess the internal and external responsiveness of the measures. Correlation coefficients between ultrasound ratios and DMC scale total and subscale scores were also calculated. RESULTS: The intrarater reliability of the DMC scale and the 4 ratios of abdominal muscle thickness varied from moderate to excellent. The DMC scale showed no floor or ceiling effects. Results for internal responsiveness of the DMC scale showed large effect sizes (2.26; 84% confidence interval [CI]: 2.06, 2.45), whereas the external responsiveness was below the proposed threshold (area under the curve = 0.54; 95% CI: 0.39, 0.68). Fair and significant correlations between some ultrasound ratios and DMC subscales were found. CONCLUSION: The DMC scale was demonstrated to be a reliable tool, with no ceiling and floor effects, and to detect change in the ability to contract the deep abdominal muscles after a lumbar stabilization exercise program, but with low accuracy for estimating patient-perceived clinical outcome.
Keywords: abdominal muscles; low back pain; motor control; ultrasound imaging